2019
DOI: 10.1136/bmjqs-2018-008372
|View full text |Cite
|
Sign up to set email alerts
|

Decisions and repercussions of second victim experiences for mothers in medicine (SAVE DR MoM)

Abstract: BackgroundThe second victim effect is defined as emotional distress experienced by providers involved in mistakes. This study characterises events contributing to the second victim effect among a diverse sample of physician mothers, describes the impact on both provider and patient and seeks to determine the association between experiencing a mistake and burnout.MethodsIn this mixed-methods study, an anonymous, cross-sectional survey was posted to an online network of over 65 000 physician mothers on 17 June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
(14 reference statements)
1
22
0
1
Order By: Relevance
“…4 The concept of a "second victim" is not new in medicine and has been addressed in previous studies. [26][27][28] It is defined by a situation in which a healthcare provider becomes a victim of the adverse event brought onto the patient due to medical errors, or other causes. These incidents have repercussions on the mental health of doctors and other healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The concept of a "second victim" is not new in medicine and has been addressed in previous studies. [26][27][28] It is defined by a situation in which a healthcare provider becomes a victim of the adverse event brought onto the patient due to medical errors, or other causes. These incidents have repercussions on the mental health of doctors and other healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…. (8)(9)(10)(11)(12)(13)(14) Good (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) Adapted from Hoey et al 10…”
unclassified
“…We selected the groups due to their large size, high level of participant engagement, group guidelines requiring all members to be both physicians and mothers (including pregnant women), and history of successful research col-laborations. 9,[16][17][18][19][20] The PMG has 73,369 physician members who self-identify as mothers, including pregnant, adoptive, or foster mothers. 21 The group is active with an average of 205 new posts, 6,400 comments, and 22,000 reactions and ''likes'' daily.…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…Moreover, in the era of #MeToo, physicians should confirm that the medical profession has nonimmunity to bullying, harassment, and discrimination, and act to remove these attitudes 83,86. The literature has found that women physicians may be more likely to experience negative emotional and professional outcomes related to adverse events than men and that these outcomes may be more pronounced among women with family responsibilities 87. It has been recommended that sexual harassment, mobbing and burnout awareness and training should be implemented in the medical school curriculum 83…”
Section: Primordial Prevention Of Medical Errors By Education At Medimentioning
confidence: 99%